The role of financial literacy on financial technology for women entrepreneurs in Indonesia - Lasmini, Rizki Sri; Bakar, Mohd Hafiz; Rahim, Hainnuraqma; Mohd Rafien, Nor Shahrina (International Journal of Accounting, Finance and Business, 2025)
This study explores the role of financial literacy on technology for women entrepreneurs in Indonesia mainly focused on mobile banking and blockchain technology. Utilizing a correlational research design, data were collected from a sample of 386 women entrepreneurs through a self-constructed Likert-scale questionnaire. The analysis was conducted using path analysis techniques. The findings reveal that financial literacy significantly relationship with mobile payment. Specifically, the direct effect of financial literacy and blockchain technology application was significant. These results underscore the importance of financial literacy in enhancing the effectiveness of mobile payment and blockchain technology application. The study emphasizes the need for comprehensive financial literacy programs to maximize the benefits of technological advancements in the financial sector. Empirical evidence from related literature supports the findings, indicating that higher financial literacy enables better utilization of mobile payment and blockchain technology application. The research provides valuable insights for policymakers and educational institutions aiming to improve financial literacy and leverage mobile payment and blockchain technology application for financial management of women entrepreneurs.